DEVELOPMENT OF DA'WAH BASED ON INFORMATION AND COMMUNICATION TECHNOLOGY - Budi Ansary Lubis; Misnan Al jawi; Mailin Mailin (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2021)
ABSTRACTInformation technology (IT) is advancing rapidly and coupled with various innovations that can bring people closer or closer to religious understanding. Currently, there are almost no limits for humans to communicate, they can communicate anytime and anywhere. The development of information does not wait for days, hours, or minutes, but in a matter of seconds a variety of new information can be found on the internet. Da'wah through social media (online) is delivered faster. With just one post, you can reach a wide audience. The implication of using IT is that there needs to be good intentions, good morals and caution so as not to get caught up in things that are not expected from the use of IT. In this digital era, from children to adults, almost all use the role of technology in their daily lives. Likewise with students who take advantage of the role of technology as an activity in carrying out da'wah activities in the campus environment. The development of Da'wah which is increasingly in the position of many enthusiasts with information that is conveyed directly by the wider community. Keywords: Da'wah, Islamic Technology, Communication.